2017
DOI: 10.1177/0004867416686694
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized, placebo-controlled trial of Lactobacillus helveticus and Bifidobacterium longum for the symptoms of depression

Abstract: Objectives:This trial investigated whether probiotics improved mood, stress and anxiety in a sample selected for low mood. We also tested whether the presence or severity of irritable bowel syndrome symptoms, and levels of proinflammatory cytokines, brain-derived neurotrophic factor and other blood markers, would predict or impact treatment response.Method:Seventy-nine participants (10 dropouts) not currently taking psychotropic medications with at least moderate scores on self-report mood measures were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
224
3
34

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(272 citation statements)
references
References 50 publications
4
224
3
34
Order By: Relevance
“…Supplementary Table S1 shows characteristics of all the individual trials that have assessed probiotic interventions on depressive symptoms included in the systematic reviews . All individual studies were randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table S1 shows characteristics of all the individual trials that have assessed probiotic interventions on depressive symptoms included in the systematic reviews . All individual studies were randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in some previous publications(McFarland, 2014;Romijn et al, 2017), probiotics may have a beneficial effect on mood or psychological symptoms in healthy subjects but no significant effect in subjects with mental or physical illness. As illustrated in some previous publications(McFarland, 2014;Romijn et al, 2017), probiotics may have a beneficial effect on mood or psychological symptoms in healthy subjects but no significant effect in subjects with mental or physical illness.…”
mentioning
confidence: 79%
“…The remaining 12(Begtrup et al, 2013;Feher et al, 2014;Guyonnet et al, 2007;Kato-Kataoka et al, 2016;Lorenzo-Zuniga et al, 2014;Lyra et al, 2016;Marcos et al, 2004;Ostlund-Lagerstrom et al, 2016;Pinto-Sanchez et al, 2017;Romijn, Rucklidge, Kuijer, & Frampton, 2017;Steenbergen, Sellaro, van Hemert, Bosch, & Colzato, 2015;Stevenson et al, 2014) studies were included in the quantitative meta-analyses. After removing duplicate results, there remained 1,050 studies, of which 1,010 were subsequently excluded in the title and abstract screening step.…”
mentioning
confidence: 99%
“…While the popular media tend to focus on psychobiotic clinical trials that achieve positive results, negative results are also quite common. For example, a recent double-blind, placebo-controlled RCT investigating the efficacy of probiotics in the treatment of depression found no marked difference in outcomes between the placebo and probiotic groups [71]. A meta-analysis of RCTs investigating the efficacy of psychobiotics in treating anxiety and depression revealed that many RCTs report different results, with overall preliminary evidence existing to tentatively support the use of psychobiotics in treating these disorders [72].…”
Section: Behavior Modulation and The Intestinal Microbiotamentioning
confidence: 99%